2014
DOI: 10.1186/1471-2431-14-219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of the vitamin K dependent coagulation system and intraventricular hemorrhage in preterm infants

Abstract: BackgroundPathogenesis of intraventricular hemorrhage (IVH) in premature infants is multifactorial. Little is known about the impact of genetic variants in the vitamin K-dependent coagulation system on the development of IVH.MethodsPolymorphisms in the genes encoding vitamin K epoxide reductase complex 1 (VKORC1 -1639G>A) and coagulation factor 7 (F7 -323Ins10) were examined prospectively in 90 preterm infants <32 weeks gestational age with respect to coagulation profile and IVH risk.ResultsF7-323Ins10 was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Several reports have revealed that genetic factors can influence the vitamin K-dependent coagulation system and intraventricular hemorrhage [14,15]. Further studies regarding the usefulness of testing for genetic variants to prevent and diagnose VKDB are warranted.…”
Section: Diagnosis Of Vkdb In Infancymentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have revealed that genetic factors can influence the vitamin K-dependent coagulation system and intraventricular hemorrhage [14,15]. Further studies regarding the usefulness of testing for genetic variants to prevent and diagnose VKDB are warranted.…”
Section: Diagnosis Of Vkdb In Infancymentioning
confidence: 99%
“…A frequent single nucleotide polymorphism (SNP)-G-1639A-within the VKORC1 promoter has been identified as a major determinant of coumarin sensitivity, reducing the activity of vitamin K epoxide reductase enzyme to 50% of that of the wild GG type. Polymorphisms in VKORC1 (G-1639A) and coagulation factor 7 (F7-323 Ins10) were reportedly associated with intraventricular hemorrhage or low factor VII levels [14]. Recently, the presence of variant alleles in VKORC1 (SNP: rs9923231) was reportedly associated with vitamin K deficiency bleeding (VKDB) [15].…”
Section: Introductionmentioning
confidence: 99%
“…24,31 One 24 of two studies found decreased FX activity in neonates with IVH. 24,31 A combined FII/VII/X activity assay was used in two studies, with no significant difference observed between the two groups of neonates. 38,40 Eight studies measured fibrinogen concentration, 10,11,23 25,35,37,39,40 among which seven reported no difference between the two groups.…”
Section: Secondary Hemostasismentioning
confidence: 99%
“…27 Finally, the role of vitamin K in IVH has been investigated across the past 20 years, and a recent unreplicated study of polymorphisms in genes encoding vitamin D epoxide reductase complex 1 (VKORC1 – 1639G>A) and coagulation factor 7 (F7-323Ins10) suggests that genetic variants in the vitamin K-dependent coagulation system influence IVH risk in preterm infants, although further studies are necessary. 50 …”
Section: Clinical Studies Suggest Coagulation Inflammation and Vascumentioning
confidence: 99%